Search for 3- and 4-body decays of the scalar top quark in pp̄ collisions at √s=1.8 TeV - Abazov, V; Abbott, B; Abdesselam, A; Abolins, M; Abramov, V; Acharya, B; Adams, D; Adams, M; Ahmed, SN; Alexeev, G; Alton, A; Alves, G; et al. (2004)
We have searched for the signature of 3- and 4-body decays of pair-produced scalar top quarks (stop) in the inclusive final state containing an electron, a muon, and significant missing transverse energy using a sample of pp̄ events corresponding to 108.3 pb-1 of data collected with the DØ detector at Fermilab. The search is done in the framework of the minimal supersymmetric standard model assuming that the neutralino (χ̃10) is the lightest supersymmetric particle and is stable. No evidence for a signal is found and we derive cross-section upper limits as a function of stop (t̃) and neutralino masses in different decay scenarios leading to the bℓνχ̃10 final state. © 2004 Published by Elsevier B.V.